CHARACTERIZATION OF A CHITOSAN/POLYANILINE FILM LOADED WITH LOVASTATIN - Thanh Nga, Bui; Xuan Mai, Huynh; Quoc Manh, Vu; Dang Dat, Nguyen; Thi Huong, Vu; Quoc Trung, Vu (HNUE Journal of Science: Journal of Natural Sciences, 2025)
This research aims to address these challenges by dispersing the drug within both a single biopolymer matrix (chitosan) and a dual biopolymer matrix (chitosan/polyaniline). The results indicated that, among the single-matrix chitosan/lovastatin (CsL) samples, the CsL10 CsL10 exhibits the most favorable drug-release behavior over 30 h, achieving a cumulative release of 96% in simulated intestinal fluid (pH 7.4) while providing effective drug protection of 10.5% in simulated gastric fluid (pH 2.0). These findings suggest a promising platform for further development. Building upon this direction, the study was extended to incorporate polyaniline to enable live-function monitoring and tissue stimulation. The results showed that the chitosan/polyaniline/lovastatin (CsPL) samples met the initial expectations, with the CsPL7 sample exhibiting drug release rates of 92.23% and 18.58% in the simulated intestinal and gastric environments, respectively. Analytical techniques, including FT-IR, FESEM, DSC, and UV-Vis, were employed to gain a deeper understanding of the interactions between the polymer components and the drug substance.